Effect of Race on Prediction of Brain Amyloidosis by Plasma Aβ42/Aβ40, Phosphorylated Tau, and Neurofilament Light. (19th July 2022) - Schindler, Suzanne E.; Karikari, Thomas K.; Ashton, Nicholas J.; Henson, Rachel L.; Yarasheski, Kevin E.; West, Tim; Meyer, Mathew R.; Kirmess, Kristopher M.; Li, Yan; Saef, Benjamin; Moulder, Krista L.; Bradford, David; et al.
Abstract : Background and Objectives: To evaluate whether plasma biomarkers of amyloid (Aβ42/Aβ40), tau (p-tau181 and p-tau231), and neuroaxonal injury (neurofilament light chain [NfL]) detect brain amyloidosis consistently across racial groups. Methods: Individuals enrolled in studies of memory and aging who self-identified as African American (AA) were matched 1:1 to self-identified non-Hispanic White (NHW) individuals by age, APOE ε4 carrier status, and cognitive status. Each participant underwent blood and CSF collection, and amyloid PET was performed in 103 participants (68%). Plasma Aβ42/Aβ40 was measured by a high-performance immunoprecipitation–mass spectrometry assay. Plasma p-tau181, p-tau231, and NfL were measured by Simoa immunoassays. CSF Aβ42/Aβ40 and amyloid PET status were used as primary and secondary reference standards of brain amyloidosis, respectively. Results: There were 76 matched pairs of AA and NHW participants (n = 152 total). For both AA and NHW groups, the median age was 68.4 years, 42% were APOE ε4 carriers, and 91% were cognitively normal. AA were less likely than NHW participants to have brain amyloidosis by CSF Aβ42/Aβ40 (22% vs 43% positive; p = 0.003). The receiver operating characteristic area under the curve of CSF Aβ42/Aβ40 status with the plasma biomarkers was as follows: Aβ42/Aβ40, 0.86 (95% CI 0.79–0.92); p-tau181, 0.76 (0.68–0.84); p-tau231, 0.69 (0.60–0.78); and NfL, 0.64 (0.55–0.73). In models predicting CSF Aβ42/Aβ40 status with plasma Aβ42/Aβ40 that included covariates (age, sex, APOE ε4 carrier status, race, and cognitive status), race did not affect the probability of CSF Aβ42/Aβ40 positivity. In similar models based on plasma p-tau181, p-tau231, or NfL, AA participants had a lower probability of CSF Aβ42/Aβ40 positivity (odds ratio 0.31 [95% CI 0.13–0.73], 0.30 [0.13–0.71], and 0.27 [0.12–0.64], respectively). Models of amyloid PET status yielded similar findings. Discussion: Models predicting brain amyloidosis using a high-performance plasma Aβ42/Aβ40 assay may provide an accurate and consistent measure of brain amyloidosis across AA and NHW groups, but models based on plasma p-tau181, p-tau231, and NfL may perform inconsistently and could result in disproportionate misdiagnosis of AA individuals.